Vorapaxar in Patients With Diabetes Mellitus and Previous Myocardial Infarction. Issue 12 (24th March 2015) - Cavender, Matthew A.; Scirica, Benjamin M.; Bonaca, Marc P.; Angiolillo, Dominick J.; Dalby, Anthony J.; Dellborg, Mikael; Morais, Joao; Murphy, Sabina A.; Ophuis, Ton Oude; Tendera, Michal; Braunwald, Eugene; Morrow, David A.
<x xml:space="preserve">Abstract</x> Background— Vorapaxar reduces cardiovascular death, myocardial infarction (MI), or stroke in patients with previous MI while increasing bleeding. Patients with diabetes mellitus (DM) are at high risk of recurrent thrombotic events despite standard therapy and may derive particular benefit from antithrombotic therapies. The Thrombin Receptor Antagonist in Secondary Prevention of Atherothrombotic Ischemic Events-TIMI 50 trial was a randomized, double-blind, placebo-controlled trial of vorapaxar in patients with stable atherosclerosis. Methods and Results— We examined the efficacy of vorapaxar in patients with and without DM who qualified for the trial with a previous MI. Because vorapaxar is contraindicated in patients with a history of stroke or transient ischemic attack, the analysis (n=16 896) excluded such patients. The primary end point of cardiovascular death, MI, or stroke occurred more frequently in patients with DM than in patients without DM (rates in placebo group: 14.3% versus 7.6%; adjusted hazard ratio, 1.47; P<0.001). In patients with DM (n=3623), vorapaxar significantly reduced the primary end point (11.4% versus 14.3%; hazard ratio, 0.73 [95% confidence interval, 0.60–0.89]; P=0.002) with a number needed to treat to avoid 1 major cardiovascular event of 29. The incidence of moderate/severe bleeding was increased with vorapaxar in patients with DM (4.4% versus 2.6%; hazard ratio, 1.60 [95% confidence interval, 1.07–2.40]). However, net clinical outcome integrating these 2 end points (efficacy and safety) was improved with vorapaxar (hazard ratio, 0.79 [95% confidence interval, 0.67–0.93]). Conclusions— In patients with previous MI and DM, the addition of vorapaxar to standard therapy significantly reduced the risk of major vascular events with greater potential for absolute benefit in this group at high risk of recurrent ischemic events. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00526474.